SWATH-MS reveals that bisphenol A and its analogs regulate pathways leading to disruption in insulin signaling and fatty acid metabolism - Kulsange, Shabda E.; Sharma, Monika; Sonawane, Babasaheb; Jaiswal, Meera R.; Kulkarni, Mahesh J.; Santhakumari, B. (Food and Chemical Toxicology, 2024)
Bisphenol A (BPA) is an endocrine-disrupting chemical (EDC), associated with obesity and insulin resistance. The FDA prohibited the use of BPA-based polycarbonate resins in infant formula packaging; thus, its analogs, viz. Bisphenol S (BPS) and Bisphenol F (BPF) were considered alternatives in epoxy resins, plastics, and food cans. As these analogs might evoke a similar response, we investigated the role of Bisphenols (BPA, BPF, and BPS), on insulin signaling in CHO-HIRc-myc-GLUT4eGFP cells at environmentally relevant concentrations of 2 nM and 200 nM. Insulin signaling demonstrated that Bisphenols reduced phosphorylation of IR and AKT2, GLUT4 translocation, and glucose uptake. This was accompanied by increased oxidative stress. Furthermore, SWATHMS-based proteomics of 3T3-L1 cells demonstrated that Bisphenol-treated cells regulate proteins in insulin resistance, adipogenesis, and fatty acid metabolism pathways differently. All three Bisphenols induced differentially expressed proteins enriched similar pathways, although their abundance differed for each Bisphenol. This might be due to their varying toxicity level, structural differences, and estrogen-mimetic activity. This study has important implications in addressing health concerns related to EDCs. Given that the analogs of BPA are considered alternatives to BPA, the findings of this study suggest they are equally potent in altering fatty acid metabolism and inducing insulin resistance.
Keywords: Bisphenols; Estrogen; Lipid droplet; Mitochondrial beta-oxidation; Oxidative stress; PPAR gamma